Jane Franklin (1791-1875) - Rahmani, Geraldine (ARCTIC, 1983)
Jane Franklin, nee Griffin, was born December 1791 of Huguenot stock. She was educated, lively, and curious. At the age of 17 she visited the hold of a prison ship and later visited other prisons - places where European women had not before ventured. Jane was a very good friend of Franklin's first wife, the poetess, Eleanor Porden. A year after Eleanor's death from tuberculosis, Jane and John Franklin were married. In 1830, Jane accompanied her husband to Van Dieman's Land (Tasmania), where he served as Lieutenant-Governor of a penal colony. It was here that Jane's interest in travel and social reform blossomed. She was the first woman to climb Mount Wellington and to travel overland from Melbourne to Sydney. To encourage free immigration she established an agricultural settlement on the Huon River. She also attempted to improve conditions for female convicts. While Franklin was engaged in searching for the Northwest Passage, Lady Franklin travelled to the West Indies and the United States, where she climbed Mount Washington. When uneasiness about the Franklin expedition became expressed by the Admiralty, Lady Franklin contributed 3000 [Pounds Sterling] to any ship making extreme exertions in the attempt of finding Franklin's ship or survivors. She tirelessly supported search efforts for many years to come, contacting Russia and the United States for their support, as well. She placed her last hopes on Leopold McClintock who commanded the Fox, which had been purchased and refurbished at Lady Franklin's expense. In September 1859 McClintock returned with relics of the expedition and a document which told part of the story. Lady Franklin continued to travel widely throughout her life, visiting the United States, South America, Hawaii, Japan, China, India, and Africa. .